Escherichia coli infection induces mucosal damage and expression of proteins promoting urinary stone formation - Tarmono Djojodimedjo (Springer, 2013)
The effect of urinary tract infection (UTI) on mucosal damage and production of proteins promoting urinary stone formation has not been elucidated. Osteopontin production, with associated mucosal damage due to UTI, may allow easier crystal retention and nucleation resulting in stone formation. The aim of this study is to demonstrate that expression of osteopontin (OPN), OPN mRNA, TLR-4, JNK, TNFR-1, iNOS, HMGB-1, and apoptosis process is higher than normal at renal tubular cells due to urinary tract infection by Escherichia coli. Adult male New Zealand strain rabbits were used. Thirty New Zealand strain rabbits were divided into three groups. The first group acted as controls, the second group underwent ligation of right ureter, and the third group underwent ligation of right ureter and injection of Escherichia coli 105/ml proximal to ligation. Nephrectomy and histological examination were performed after 5 days. All groups were HE stained to examine mucosal damage, specific monoclonal antibodies for TLR-4, JNK, mRNA OPN, OPN, TNFR-1, iNOS and HMGB-1. Apoptotic nuclei were demonstrated using TUNEL method. Statistical calculations were performed using ANOVA test, with p < 0.05 considered significant. The findings confirmed the hypothesis that infection of urinary tract by Escherichia coli demonstrated higher expression of OPN, OPN mRNA, TLR-4, JNK, TNFR-1, iNOS, HMGB-1, apoptosis process and mucosal damage than normal. Infection of urinary tract by Escherichia coli caused higher than normal expression of promoter protein osteopontin and mucosal damage at renal tubular cells. These suggest that urinary infection may promote stone formation by mucosal damage and elevate promoter protein osteopontin at tubulus cell, allowing easier crystal retention and nucleation.